2022
DOI: 10.3390/ijms23095075
|View full text |Cite
|
Sign up to set email alerts
|

Elevated LSD1 and SNAIL Expression Indicate Poor Prognosis in Hypopharynx Carcinoma

Abstract: Head and neck squamous cell carcinomas (HNSCC) are among the most common cancers worldwide and are associated with a poor prognosis for patients. Among HNSCC, those originating in the hypopharynx have the worst prognosis. The histone demethylase LSD1 has been shown to promote cancer initiation, progression, and relapse through various mechanisms and is upregulated in many cancer tissues. LSD1 physically interacts with SNAIL and is required for SNAIL mediated transcriptional repression. Previous studies of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…We analyzed TRIM21 expression in HNSCC specimens derived from a cohort of 419 patients diagnosed between 2012 and 2015 at the Institute of Pathology of the University Medical Center Schleswig-Holstein, Germany, as reported previously [ 13 , 34 , 35 , 36 , 37 , 38 , 39 ]. Tumor samples were derived from PTs, LMs, RTs and DMs.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed TRIM21 expression in HNSCC specimens derived from a cohort of 419 patients diagnosed between 2012 and 2015 at the Institute of Pathology of the University Medical Center Schleswig-Holstein, Germany, as reported previously [ 13 , 34 , 35 , 36 , 37 , 38 , 39 ]. Tumor samples were derived from PTs, LMs, RTs and DMs.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated that overexpression of SNAIL is associated with poor prognosis in patients with hypopharynx carcinoma and breast cancer 47,48 . The mechanistic role of SNAIL attributed to MDR is expected to be better understood in light of the role of the EMT 39 .…”
Section: Emt Inducersmentioning
confidence: 99%
“…46 Previous studies demonstrated that overexpression of SNAIL is associated with poor prognosis in patients with hypopharynx carcinoma and breast cancer. 47,48 The mechanistic role of SNAIL attributed to MDR is expected to be better understood in light of the role of the EMT. 39 A review of the previous studies reveals that SNAIL overexpression increases the risk of chemoresistance, as evidenced by in vitro experiments 5-fluorouracil-resistant breast cancer cells, 49 and cisplatin-resistant ovarian cancer cells.…”
Section: Snailmentioning
confidence: 99%
“…For instance, KDM1 is overexpressed in bladder carcinomas but exhibits significantly decreased proliferation when treated with small interfering RNA (siRNA) matching to the KDM1 gene. The overexpression and carcinogenic activities of KDM1 have been also reported in breast, colorectal, liver, lung, hypopharynx, and prostate, cancers [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. This renders key candidature to LSD1/KDM1 as a possible cancer therapeutic.…”
Section: Histone Demethylase Dysregulation and Cancermentioning
confidence: 99%